2016
DOI: 10.1002/jbio.201500233
|View full text |Cite
|
Sign up to set email alerts
|

In vivo human corneal deformation analysis with a Scheimpflug camera, a critical review

Abstract: Corneal morphological analysis has greatly improved in recent years, providing physicians with new and reliable parameters to study. Moreover, today corneal functional too is a routine analysis, thanks to biomechanical evaluation allowed by an ocular response analyzer (Reichert Ophthalmic Instrument, Depew, NY, USA). Corvis ST (OCULUS Optikgeräte GmbH, Wetzlar, Germany), that relies on the ultrahigh speed Scheimpflug camera, is a new device providing corneal deformation parameters measured ny scanning the corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 95 publications
(206 reference statements)
0
23
0
Order By: Relevance
“…Differences in applied force might confound attempts to directly compare results obtained with these two instruments. 19 …”
Section: Clinical Measurements Of Corneal Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in applied force might confound attempts to directly compare results obtained with these two instruments. 19 …”
Section: Clinical Measurements Of Corneal Biomechanicsmentioning
confidence: 99%
“…21,22 Repeatability studies showed that the Corvis can produce reliable measurements of IOP and central corneal thickness (CCT), while the results are more variable when the corneal deformation and biomechanical parameters are analyzed. 19,2325 These limitations do not diminish the importance of measuring biomechanical behavior in vivo, and both devices have greatly advanced our understanding of corneal biomechanical behavior in many clinically relevant states. Studies that combine tomographic and biomechanical assessment have demonstrated enhanced refractive surgery screening potential 26,27 and suggest that many advances are yet to come in the use of biomechanical measurements for diagnosis and clinical decision making.…”
Section: Clinical Measurements Of Corneal Biomechanicsmentioning
confidence: 99%
“…The corneal response to the air puff is initially marked by an inward conformational change in the corneal curvature. This initial flattening of the cornea is referred to as the first applanation (Figure 3) [50, 55]. The cornea eventually deforms to a point where it is maximally concave prior to returning to its original shape.…”
Section: Corneal Biomechanics and Iopmentioning
confidence: 99%
“…This event defines the corneal deformation amplitude at the highest concavity (Figure 3). The cornea then naturally returns to its original shape, which is referred to as the second applanation [50, 55]. Various aspects of the corneal deformation response to the air-puff can be quantified, which are reviewed in detail elsewhere [55].…”
Section: Corneal Biomechanics and Iopmentioning
confidence: 99%
See 1 more Smart Citation